Multiple stress response of lowland stream benthic macroinvertebrates depends on habitat type - Graeber, Daniel; Jensen, Tinna M.; Rasmussen, Jes J.; Riis, Tenna; Wiberg-Larsen, Peter; Baattrup-Pedersen, Annette (The Science of the total environment, 2017)
Worldwide, lowland stream ecosystems are exposed to multiple anthropogenic stress due to the combination of water scarcity, eutrophication, and fine sedimentation. The understanding of the effects of such multiple stress on stream benthic macroinvertebrates has been growing in recent years. However, the interdependence of multiple stress and stream habitat characteristics has received little attention, although single stressor studies indicate that habitat characteristics may be decisive in shaping the macroinvertebrate response. We conducted an experiment in large outdoor flumes to assess the effects of low flow, fine sedimentation, and nutrient enrichment on the structure of the benthic macroinvertebrate community in riffle and run habitats of lowland streams. For most taxa, we found a negative effect of low flow on macroinvertebrate abundance in the riffle habitat, an effect which was mitigated by fine sedimentation for overall community composition and the dominant shredder species (Gammarus pulex) and by nutrient enrichment for the dominant grazer species (Baetis rhodani). In contrast, fine sediment in combination with low flow rapidly affected macroinvertebrate composition in the run habitat, with decreasing abundances of many species. We conclude that the effects of typical multiple stressor scenarios on lowland stream benthic macroinvertebrates are highly dependent on habitat conditions and that high habitat diversity needs to be given priority by stream managers to maximize the resilience of stream macroinvertebrate communities to multiple stress. [Display omitted] •Macroinvertebrates in runs are affected by fine sediment, not by low flow.•Strong response to low flow in riffles, mitigated by fine sediment and nutrients•Fast reaction of macroinvertebrates to low flow and fine sediment, if responses detected•Habitat dependency of effects advises habitat restoration measures.